THE ENDOCRINE PANCREAS IN BRAIN-DEAD DONORS A PROSPECTIVE STUDY IN 25 PATIENTS - Françoise Masson; MICHEL THICIIPE; H. Gin; ANDRE DE MASCAREL; R Angibeau; J. F. Favarel-Garrigues; P Erny (1993)
To determine whether hyperglycemia in brain-dead donors is a sign of endocrine pancreas insufficiency, we studied pancreatic function in 25 consecutive brain dead patients. Blood samples were drawn at 2-hr intervals from donor referral until organ procurement to analyze glucose, insulin, and C-peptide levels. After donor retrieval, two specimens were taken from the pancreas for a subsequent immunohistochemical examination. At referral mean glycemia was 13.60±1.49 mmol/L, and there was a large range of plasma glucose levels (4–6–31.6). Of 25 patients, 16 had glycemia above 10 mmol/L. At organ procurement a mean of 20 hr later, mean glycemia as 8.61±0.58 mmol/L (P<0.005 with paired t test), and only 5 patients had glycemia above 10 mmol/L. Hyperglycemia was associated with elevated insulin and C-peptide levels during donor management. An elevated C-peptide/glucose molar ratio might be considered a sign of peripheral insulin resistance. Hyperglycemia above 25 mmol/L could not be related to the amount of glucose administered during donor maintenance. Severe hyperglycemia had a natural tendency to be partly corrected. Histologic and immunohistochemical examinations were available in 17 cases and can be considered normal. It is concluded that endocrine pancreatic function can be considered effective after brain death. The mechanism of the relative insulin resistance of these patients requires further study. Blood glucose levels, in the range observed in this study, are not a good donor criterion of endocrine pancreatic function before pancreas transplantation.